STRATEGI GURU PAI DALAM MEMBANGUN KECERDASAN INTERPERSONAL SISWA : STUDI KASUS DI MADRASAH ALIYAH RAUDLATUL MUTA’ALLIMIN KREJENGAN - Islamiatul Ula; Edi Kurniawan Farid; Nur’amin Nur’amin (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the strategies used by Islamic Religious Education (IRE) teachers in developing students’ interpersonal intelligence at Raudlatul Muta’allimin Senior High School in Krejengan. The study was motivated by the importance of developing students’ interpersonal intelligence as a key aspect in fostering social skills, communication, cooperation, and empathy. This study employs a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation involving PAI teachers and students. Data analysis was conducted through data reduction, data presentation, and drawing conclusions with validity testing using triangulation. The results of the study indicate that PAI teachers implement strategies such as religious habit formation, group discussion methods, cooperative activities, and teacher modeling through daily attitudes and behaviors. These strategies were able to improve students’ communication, cooperation, and empathy skills. The implications of the study indicate that the application of learning strategies integrated with Islamic values can support the development of students’ interpersonal intelligence more effectively, although it is still influenced by students’ internal and external factors.